Designing English Learning Interactive Multimedia Based On The 2013 Curriculum - Hidayat, Syaiful Rohman; Hermayawati, Hermayawati ((JELE) Journal Of English Language and Education, 2016)
AbstractThe research aimed at designing English Learning Interactive Multimedia (ELIM) in SMAN 1 Sedayu based on the 2013 Curriculum. This was Research and Development (R&D) study using ADDIE model. There were five stages in conducting the research; (1) Analysis; (2) Design; (3) Development; (4) Implementation; (5) Evaluation. This research involved 32 students of grade tenth of SMAN 1 Sedayu. To gain the Needs Analysis (NA), the researcher used observation, questionnaire, interview, and documentation. This researcher found a learning software program namely English Learning Interactive Multimedia (ELIM) based on the 2013 curriculum. It consists of two unit materials; ‘Malin Kundang’, and ‘Let Us Sing a Song’. It was appropriate with the 2013 Curriculum and Needs Analysis based on (1) a media and content expert judgment from Mercu Buana University of Yogyakarta; (2) the Focus Group Discussion from English teacher and students of SMA N 1 Sedayu; (3) the results of pre-test and posttest in two cycles which showed an improvement. Based on the findings above, it is recommended for the further researcher to develop the designed ELIM become the appropriate media based on the needs and condition of the research setting.